2014
DOI: 10.1007/s11011-014-9560-1
|View full text |Cite
|
Sign up to set email alerts
|

GABA receptors in brain development, function, and injury

Abstract: This review presents a brief overview of the γ-aminobutyric acid (GABA) system in the developing and mature central nervous system (CNS) and its potential connections to pathologies of the CNS. γ-aminobutyric acid (GABA) is a major neurotransmitter expressed from the embryonic stage and throughout life. At an early developmental stage, GABA acts in an excitatory manner and is implicated in many processes of neurogenesis, including neuronal proliferation, migration, differentiation, and preliminary circuit-buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
184
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(192 citation statements)
references
References 90 publications
(149 reference statements)
4
184
0
4
Order By: Relevance
“…The immature rat brain is particularly sensitive to excitotoxicity in the neonatal period [80,81]. This is regulated, in part, by developmental changes in expression of the NR2A and NR2B subunits of the NMDA receptor [82,83] and/or GABAergic neurotransmission impairments through, for example, cortical loss of GABAergic interneurons [84,85]. In the second and third postnatal weeks, however, this effect is reduced.…”
Section: Age-at-injury Response To Preclinical Tbimentioning
confidence: 99%
“…The immature rat brain is particularly sensitive to excitotoxicity in the neonatal period [80,81]. This is regulated, in part, by developmental changes in expression of the NR2A and NR2B subunits of the NMDA receptor [82,83] and/or GABAergic neurotransmission impairments through, for example, cortical loss of GABAergic interneurons [84,85]. In the second and third postnatal weeks, however, this effect is reduced.…”
Section: Age-at-injury Response To Preclinical Tbimentioning
confidence: 99%
“…Brain ischemia is also characterized by a downregulation of GABAergic synaptic transmission, both at the pre-and postsynaptic levels [3,4], but the mechanisms involved are not fully understood. Recent studies showed a decrease in the interaction of GABA A receptors (GABA A R) with the scaffold protein gephyrin in cultured hippocampal neurons subjected to oxygen-glucose deprivation (OGD), an in vitro model of brain ischemia, by a mechanism dependent on protein phosphatase activity [5].…”
Section: Introductionmentioning
confidence: 99%
“…This could explain the lower expression of AMPA GluA1 in rats given the 300 mg/kg dose, as a higher concentration of glutamate produced by the extract caused desensitization of the receptor in the adolescent age. GABA is implicated in many processes of neurogenesis, including neuronal proliferation, migration, differentiation, and preliminary circuit‐building, as well as the development during critical periods (Wu & Sun, 2015). In the mature CNS of the adult brain, GABA acts as an inhibitory neurotransmitter via activation of the fast hyperpolarizing GABA A receptors.…”
Section: Discussionmentioning
confidence: 99%